Effect of Butoconazole Nitrate 2% Vaginal Cream and Miconazole Nitrate 2% Vaginal Cream Treatments in Patients with Vulvovaginal Candidiasis - Myra A. Lappin; Doris C. Brooker; Carol A. Francisco; Joan Dorfman (Hindawi Limited, 1996)
In a multicenter, randomized, invesgtigator-blind, parallel study, 398 patients were dispensed topical butoconazole nitrate 2% cream for 3 days (n = 199) or miconazole nitrate 2% cream for 7 days (n = 199) for vaginal use. Efficacy analyses included 254 patients with culture-confirmed Candida (119 butoconazole and 135 miconazole users). Of the 398 patients issued study medication, 9 were lost to follow-up. Therefore, safety analyses included 389 patients (197 butoconazole and 192 miconazole users). Evaluations upon admission and approximately 8 and 30 days post-treatment included Candida cultures, potassium hydroxide (KOH) wet mounts, and vulvovaginal examinations, with rating of vulvovaginal signs and symptoms using a 4-point scale. Rates of clinical cure (based on sign/symptom scores), microbiologic cure (based on cultures and wet mounts), and therapeutic cure (both clinical and microbiologic cures) were assessed and were to be similar between the regimens. Therapeutic cure rates were 57.8% and 61.4% for butoconazole and miconazole, respectively. Three-day butoconazole treatment was as safe and effective as 7-day miconazole therapy in treating vulvovaginal candidiasis.